Subsídios para a tomada de decisão na gestão da infraestrutura viária urbana : aplicação nos pavimentos asfálticos no município de Pato Branco-PR - Trombetta, Jairo (2010)
The urban road network paved in Brazilian cities is undergoing a process of deterioration in function of traffic requests, and growing increasingly due to weathering of the very most of the mesh to be reaching the age limit of their life cycle coupled with lack of maintenance. This constitutes concern of municipal administrations, responsible for constructing, maintaining and operating the system in order to obtain information regarding the current state of the roads and answers as to what should be done, how to do it, when and how to act this will cost the public coffers. In recent decades many studies have been directed to the establishment of methods to help managers make decisions in order to provide the road network in satisfactory condition for use. These methods need to contextualize the particularities of each municipality in order to suggest viable solutions, taking into account reliable evaluations and diagnoses to suggest the implementation of intervention measures with the most cost-effective for society. Therefore, this work has used the method of pavement condition index (PCI) to analyze portions of floors of the road network of Pato Branco - PR, can be applied across the roads. The results show a practical and realistic concept of the condition of the pavement, leaving the beneficial aspects in the use of this tool in the management of urban pavements